Real-Time Visualization of Cell Membrane Damage Using Gadolinium-Schiff Base Complex-Doped Quantum Dots - Moulick, Amitava; Heger, Zbynek; Milosavljevic, Vedran; Richtera, Lukas; Barroso-Flores, Joaquin; Merlos Rodrigo, Miguel Angel; Buchtelova, Hana; Podgajny, Robert; Hynek, David; Kopel, Pavel; Adam, Vojtech (ACS applied materials & interfaces, 2018)
Despite the importance of cell membranes for maintenance of integrity of cellular structures, there is still a lack of methods that allow simple real-time visualization of their damage. Herein, we describe gadolinium-Schiff base-doped quantum dots (GdQDs)-based probes for a fast facile spatial labeling of membrane injuries. We found that GdQDs preferentially interact through electron-rich and hydrophobic residues with a specific sequence motif of NHE-RF2 scaffold protein, exposed upon membrane damage. Such interaction results in a fast formation of intensively fluorescent droplets with a higher resolution and in a much shorter time compared to immunofluorescence using organic dye. GdQDs have high stability, brightness, and considerable cytocompatibility, which enable their use in long-term experiments in living cultures. To the best of our knowledge, this is the first report, demonstrating a method allowing real-time monitoring of membrane damage and recovery without any special requirements for instrumentation. Because of intensive brightness and simple signal pattern, GdQDs allow easy examination of interactions between cellular membranes and cell-penetrating peptides or cytostatic drugs. We anticipate that the simple and flexible method will also facilitate the studies dealing with host-pathogen interactions.
Keywords: nádorové buněčné linie; Schiff Bases; sekvence aminokyselin; Models, Molecular; cell-penetrating peptides; fluorescenční spektrometrie; Quantum Dots; Cell Membrane; gadolinium; fluorescence labeling; Cell Line, Tumor; kvantové tečky; core−shell; Gadolinium; Schiffovy báze; Peptides; Spectrometry, Fluorescence; quantum dots; molekulární modely; Humans; Amino Acid Sequence; nanotechnologies; buněčná membrána; peptidy; lidé